Improving the Quality of Feed Ingredients Using Enzymes - Kiki Haetami; Abun Abun (Jurnal Perikanan dan Kelautan, 2024)
Commercial feed contributes to the operational costs of aquaculture production activities. On the other hand, making your feed requires formulation and availability of raw materials in maintained quantity and quality. Local feed raw materials can be used as alternative ingredients. Still, one of the obstacles is several limiting factors, such as crude fiber and the binding of some essential nutrients, such as protein and minerals. Hence, nutrient utilization is low and has a direct impact on growth. Adding feed additives as sources of enzymes is considered to help speed up the digestive process so sufficient nutrients are available for growth and survival. Enzymes break down large molecules such as crude fiber starch, increasing protein and fat into forms easily digested and absorbed by fish. This paper aims to review the use of enzymes to improve the quality of fish feed ingredients. The method used is Literature Review. Improving the quality of feed raw materials with the help of enzymes can increase the quality of fish feed ingredients. Application of enzymes in fish feed as additional feed ingredients (feed additives) through the addition of commercial enzymes, enzymes from plant or animal extracts, and microbial enzymes.